Impact Of Gramya Ahara On The Pathogenesis Of Prameha W.S.R. To Diabetes Mellitus-A Conceptual Study - Badhoria, Anil; Kaundal, Ramesh; Kumar, Jatinder (International Research Journal of Ayurveda & Yoga, 2021)
Gramya Ahara Includes all types of food habits, method of preparation and various activities which causes vitiation of all doshas in the body. Charak in Rasayan Adhyaya Ayurved-Samuthaniya Pada has elaborated that Gramya Ahara chosen by the society was not successful in making inroads in community health. Sedentary lifestyle was responsible for less physical activity which became the cause of preventable diseases. Premeha patients (Diabetic patients) are increasing day by day due to wrong diet and lifestyles, so there is a need to understand the significance of Gramya Ahara in present scenario.